The role of decreased cardiolipin and impaired electron transport chain in brain damage due to cardiac arrest. (November 2018) - Tam, Jonathan; Hong, Angela; Naranjo, Peter M.; Yin, Tai; Shinozaki, Koichiro; Lampe, Joshua W.; Becker, Lance B.; Kim, Junhwan
Abstract: Ischemic brain damage is the major cause of mortality in cardiac arrest (CA). However, the molecular mechanism responsible for brain damage is not well understood. We previously found that mitochondrial state-3 respiration, which had been decreased following CA, was recovered in the kidney and liver, but not in the brain following cardiopulmonary bypass (CPB) resuscitation. Examination of mitochondria from these tissues may shed light on why the brain is the most vulnerable. In this study, adult male Sprague-Dawley rats were subjected to asphyxia-induced CA for 30 min or 30 min followed by 60 min CPB resuscitation. Mitochondria were then isolated from brain, heart, kidney, and liver tissues for examination using spectrophotometry and mass spectrometry to measure the activities of mitochondrial electron transport complexes and the cardiolipin content. We found significantly decreased complex I activity in mitochondria isolated from all four organs following CA, while complex III and IV activities remained intact. Following CPB resuscitation, complex I activity was normalized in kidney and liver, but unrecovered in brain and heart mitochondria. In addition, complex III activity in brain mitochondria was decreased by 22% with a concomitant decrease in cardiolipin following CPB resuscitation. These results suggest that of the tissues tested only brain mitochondria suffer reperfusion injury in addition to ischemic alterations, resulting in diminished overall mitochondrial respiration following resuscitation. Highlights: We found unique alterations in brain mitochondria in a rat model of CA. Decreased complex I activity is a common ischemic defect following CA. Resuscitation fails to normalize ischemic alteration in brain mitochondria. Resuscitation causes additional damage to brain mitochondria only. The unique alterations may be responsible for unrecovered brain damage.